"Can morality and ethical be reconciled?" - Giusti, Miguel (1996)
This paper offers a balance of the debate between morality (Moralitdt) and ethical life (Sittlichkeit) that acted as conceptual framework ot the controversies on morals over the past decades. lt is here shown that, in spite of the different tentatives to find a way to reconcile both paradigms, thc debate has not had a positive outcome. The reason of this failure lies in the conflicting interpretations on the notion of practical rationality. This thesis is obtained from an immanent analysis of the debate's development.